Reformatsky Reagent Promoted Acetylation of Primary and Secondary Aliphatic Alcohols Using Ethyl Acetate as an Acetyl Donor. Issue 1 (3rd January 2019) - Fujihara, Rina; Nakata, Kenya
Abstract: The reaction system of a Reformatsky reagent as a promoter and EtOAc as a solvent and acetyl donor was found to achieve efficient acetylation of a variety of primary and secondary aliphatic alcohols under mild conditions. The reaction can be carried out by a simple one‐pot operation and does not require heating. The reaction shows a high tolerance for various functional groups and chemoselectivity, such that the phenolic hydroxyl groups do not react. Furthermore, the reaction can be used for gram‐scale acetylation. Abstract : A facile and efficient acetylation reaction of primary and secondary aliphatic alcohols was achieved by using a Reformatsky reagent generated in situ from ethyliodo acetate and Zn powder in EtOAc as a solvent and acetyl donor under mild conditions. The reaction can be carried out by a simple operation, and it is applicable for various substrates and shows highly functional group tolerance.